Deteksi Risiko Jatuh Dan Pendampingan Latihan Keseimbangan Sebagai Upaya Pencegahan Risiko Jatuh Pada Lansia Di Panti Wredha Semarang - Lilik Sigit Wibisono; Fitratun Najizah; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti; Eriga yessyra Syafitri; Dana Faricha; Panji Satria Wiguna (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Falls occur due to an unintentional loss of balance resulting in a failure of postural stability, or an unexpected and sudden change in position resulting in landing on the floor. Associated risk factors include current health status (living in the community, nursing home, hospital, frail or active state), existing illness (diabetes, hip fracture, stroke) and general changes associated with aging (decreased balance, coordination, muscle strength, visual impairment, etc.). The elderly are an age group that is vulnerable to falls. The purpose of this service is to detect the risk of falls in the elderly and provide assistance in balance training as an effort to prevent the risk of falls in the elderly. The output targets to be achieved are in the form of accredited national journal publications and Copyright for videos of community service activities. The method used is a fall risk detection examination using the Time Up and Go Test and continued with the provision of balance training, so that the elderly who have a risk of falling can be recognized as early as possible so that the provision of balance training can maintain and improve the balance of the elderly body.